2021
DOI: 10.1007/s10933-021-00222-9
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and climate sensitivity of a groundwater-fed lake on subtropical North Stradbroke Island (Minjerribah), Queensland, Australia over the last 7500 years

Abstract: Lake sediments are important archives of past climate variability and lake responses to climate. In order to accurately infer past climates, it is necessary to understand, and account for, the ecological processes that affect the record of indicators preserved in lake sediment. This is particularly the case with respect to the concentration of carbon and nitrogen (TOC, TN, and calculated C:N), and the stable isotope composition of organic matter preserved in lake sediments. These are common, yet ambiguous, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…This complexity is reflected in the remaining ∼50% of total variance which is not accounted for by canonical axes I and II. Some of the processes not accounted for in this study may be attributed to TOC/TN ratios of topsoil and leaf litter in the range of aquatic OM (<10–20, Holtvoeth et al., 2016; Forbes et al., 2021; Maxson, Tibby, Barr, et al., 2021), as well as different degrees of soil‐organic matter decomposition in the catchments across the sites studied herein. Most significantly, TOC/TN < 4 in combination with low TOC, as reported for Booberoi Lagoon (MDB‐QLD), Moira Lake (MDB‐NSW (south)), and 2 Carp Billabong (MDB‐VIC), can be attributed to decomposition controlling C‐loss and clay‐bound ammonium supply from the catchment promoting increasing N concentrations (Francke et al., 2016; Holtvoeth et al., 2016).…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…This complexity is reflected in the remaining ∼50% of total variance which is not accounted for by canonical axes I and II. Some of the processes not accounted for in this study may be attributed to TOC/TN ratios of topsoil and leaf litter in the range of aquatic OM (<10–20, Holtvoeth et al., 2016; Forbes et al., 2021; Maxson, Tibby, Barr, et al., 2021), as well as different degrees of soil‐organic matter decomposition in the catchments across the sites studied herein. Most significantly, TOC/TN < 4 in combination with low TOC, as reported for Booberoi Lagoon (MDB‐QLD), Moira Lake (MDB‐NSW (south)), and 2 Carp Billabong (MDB‐VIC), can be attributed to decomposition controlling C‐loss and clay‐bound ammonium supply from the catchment promoting increasing N concentrations (Francke et al., 2016; Holtvoeth et al., 2016).…”
Section: Discussionmentioning
confidence: 82%
“…TOC/TN and δ 13 C from Bishops Swamp, located in the vicinity of the MDB along the east coast of NSW, suggest a more terrestrial dominated organic matter source (Figure 2). Values from the three North Stradbroke Island sites plot outside the traditionally defined range for both aquatic and C3 dominated organic matter, which may reflect a mixture of aquatic and terrestrial‐derived organic sources as well as additional processes affecting TOC/TN and δ 13 C. Previous studies demonstrated that organic matter accumulated in Blue Lake and other North Stradbroke Island sites (Cadd et al., 2018; Maxson, Tibby, Barr, et al., 2021; Maxson, Tibby, Marshal, et al., 2021) is predominantly of aquatic origin, despite an elemental and carbon isotope signature more characteristic for terrestrial sources. This has been attributed to N‐limitation artificially increasing TOC/TN, similar to the process described for Tasmania (Maxson, Tibby, Barr, et al., 2021; Maxson, Tibby, Marshal, et al., 2021).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations